Primjena digitalnih mjerila u pohranjivanju etalona : doktorska disertacija - Ilić, Damir; Butorac, Josip (Zagreb : D. Ilić ; Fakultet elektrotehnike i računarstva, 1999)
U uvodnom dijelu pregledno je prikazan sadržaj svih poglavlja, ukratko su opisane razvijene mjerne metode i analizirani ostvareni mjerni rezultati te njihova primjena.
Vrhunsko mjeriteljstvo električkih veličina opisano je u drugom poglavlju. Zbog toga ovdje nalazimo ustrojstvo SI sustava jedinica, načelo rada uređaja za utjelovljenje jedinica električke struje i napona, opis računskog etalona kapaciteta te metodâ za usporedbu etalona otpora s etalonima kapaciteta u vrhunskoj točnosti. Osim toga prikazani su i kvantni etaloni napona i otpora, kojima se danas volt i om pohranjuju s najmanjom nesigurnošću.
Treće poglavlje posvećeno je Primarnom elektromagnetskom laboratoriju, koji djeluje u sklopu Fakulteta elektrotehnike i računarstva Sveučilišta u Zagrebu. Opisano je ustrojstvo Laboratorija te slijedni sustav za osnovne elektromagnetske veličine: napon, otpor, kapacitet i frekvenciju. Detaljno su prikazani referentni etaloni koji čine etalonsku osnovu Laboratorija i osiguravaju sljedivost prema međunarodnom sustavu, a to su: elektronički etalon napona s osnovnom razinom 10 V, etaloni otpora od 1 Ω i 10 kΩ, kremeni i zračni etalon kapaciteta od 100 pF te etalon otpora od 100 MΩ vlastite konstrukcije. Na kraju ovog poglavlja opisan je digitalni multimetar HP 3458A, s kojim se napon mjeri do rezolucije od 8½ znamenaka. To je osnovno digitalno mjerilo koje je rabljeno u mjernim metodama za mjerenje efektivne vrijednosti izmjeničnog napona niske frekvencije i faznog pomaka između dva napona, a njime su provedena mjerenja kojih su rezultati prikazani u šestom poglavlju.
Za pohranjivanje referentnih etalona otpora u Laboratoriju je konstruiran uljni ultratermostat UTEO-97, koji je prikazan u četvrtom poglavlju. U tom su ultratermostatu za regulaciju temperature primijenjeni NTC otpornici, a kako bi se iz svake izmjerene vrijednosti otpora odredila mjerena temperatura, na temelju dostupnih (tabličnih) podataka određena je nadomjesna krivulja. Prikazano je umjeravanje ukupno 30 NTC otpornika i određivanje pripadnih parametara nadomjesne krivulje. Regulacija referentne temperature od 23 °C u ultratermostatu izvedena je uz računalom upravljan mjerni sustav, u kojem se otpor NTC osjetila izravno mjeri digitalnim multimetrom, dok računalo služi za prikupljanje mjernih podataka, računanje parametara regulacije te ugađanje potrebnih regulacijskih napona preko ugrađenog D/A sučelja. Prikazana je ostvarena stalnost temperature uz navedeni način regulacije i dogrijavanje ulja do referentne temperature, koja tijekom jednog dana može biti bolja od ±1 mK, a u dužem vremenskom razdoblju redovito bolja od ±10 mK.
U petom poglavlju prikazana je metoda usporedbe etalona otpora od 100 MΩ s etalonom kapaciteta od 100 pF s pomoću digitalnih voltmetara HP 3458A upravljanih računalom, koja se u Laboratoriju rabi za prenošenje sljedivosti s područja kapaciteta na područje otpora, tj. C→R usporedbu. U tu se svrhu slaže mjerni most u čijoj se jednoj grani nalazi otporničko djelilo omjera 1000:1, a u drugoj grani se, kao gornji element djelila, postavlja etalonski otpornik od 100 MΩ kad se mjerenje obavlja istosmjernom strujom, odnosno etalonski kondenzator od 100 pF kad se mjerenje obavlja izmjeničnom strujom. I u toj grani je omjer dijeljenja 1000:1, jer je donji element djelila etalon otpora od 100 kΩ, dok digitalni voltmetri u oba slučaja mjere napone u dvjema granama mosta na donjem elementu. Analize pokazuju da je očekivana nesigurnost ove metode oko 0,1×10−6, jer je za određivanje otpora etalona od 100 MΩ prema etalonu kapaciteta od 100 pF potrebno poznavati omjere naponâ kod istosmjerne i izmjenične struje. Pritom je detaljno analizirana metoda mjerenja izmjeničnog napona frekvencije 15,873 Hz kad je voltmetar postavljen na istosmjerno naponsko područje te integrira mjereni izmjenični napon tijekom jedne trećine njegove periode (21 ms). Uzorci se uzimaju pomicanjem početka integracije uvijek za isti interval tako da njihove vrijednosti također slijede sinusni valni oblik kao i mjereni napon, odnosno govorimo o “izvedenoj” sinusoidi. Uzimanje uzoraka s frekvencijom koja se razlikuje od frekvencije mjerenog napona ima za posljedicu necijeli broj uzoraka po periodi “izvedene” sinusoide pa je prikazana metoda provlačenja polinoma petog stupnja kroz sumu kvadrata uzoraka u okolišu ništice, kojom se na ispravan način računa efektivna vrijednost “izvedene” sinusoide i u tom slučaju. Opisano je određivanje nepoznatih kapaciteta u granama mosta metodom paralelnog spajanja kapaciteta poznatog iznosa, a posebno je analizirana mogućnost njihovog određivanja mjerenjem faznog pomaka između napona na donjem elementu djelila i ukupnog napona.
Šesto poglavlje sadrži analize i rezultate mjerenja faznog pomaka između dvaju napona, mjerenih digitalnim voltmetrima HP 3458A, prema postavkama opisanim u prethodnom poglavlju. Mjerni postupak je automatiziran jer su voltmetri povezani s računalom, koje se rabi za upravljanje mjernim uređajima te za prihvat, analizu i zapis mjernih rezultata. Poglavlje započinje prikazom metode za određivanje početnog faznog kuta “izvedene” sinusoide, koja se temelji na računanju kuta za svaki uzorak “izvedene” sinusoide i provlačenju pravca regresije kroz tako izračunate kuteve. Koeficijent b tog pravca određuje traženi početni fazni kut, a iz razlike dvaju početnih faznih kuteva računa se onda fazni pomak između dva napona. Opisan je standardni mjerni postupak, u kojem se digitalnim voltmetrima mjere dva napona frekvencije 15,873 Hz od omjera amplituda 1:1 do 1000:1 tako da se uzima ukupno 2381 uzorak “izvedene” sinusoide, te za svaki od njih računa srednja vrijednost, efektivna vrijednost i početni fazni kut kako bi se onda izračunao i njihov fazni pomak. Pritom se zbog mjerenja kuteva rabi sinkroni način okidanja voltmetara, kod kojeg je jedan voltmetar “glavni” i on generira okidne impulse koji se prenose “slijednom” voltmetru. Da bi tako izračunati fazni pomak bio ispravan potrebno je uzeti u obzir korekciju, koja ovisi o mjernim opsezima na koje su voltmetri postavljeni te o slijedu okidanja. Analizirana je i eksperimentalno potvrđena metoda određivanja korekcije faznog pomaka za sve kombinacije mjernih opsega od 100 mV do 1000 V. Ona se temelji na kaskadnom mjerenju istog napona dvama voltmetrima koji su prvo postavljeni na iste mjerne opsege, a nakon toga se mjerenje ponavlja uz jedan voltmetar postavljen na prvi viši mjerni opseg. U ovom poglavlju prikazani su rezultati mjerenja korekcijâ faznog pomaka za dva para voltmetara (četiri) HP 3458A opisanom metodom, koje su određene s nesigurnošću od 0,1 µrad. Te se vrijednosti rabe kod mjerenja faznog pomaka naponâ djelila, kojeg čine etalon kapaciteta od 100 pF i etalon otpora od 100 kΩ; pritom se iz izmjerenog faznog pomaka određuje nepoznati parazitni kapacitet koji se nalazi paralelno etalonu otpora, a kojemu doprinos daje i ulazni kapacitet samog voltmetra, pa se može kazati da neizravno voltmetar sam sebi mjeri vlastiti kapacitet. Ovo mjerenje je potrebno kako bi se odredio jedan od koeficijenata (korekcijskih faktora) kod prijelaza sa 100 pF na 100 MΩ metodom opisanom u petom poglavlju. Drugi koeficijent (korekcijski faktor) za istu metodu ovisi o kompenziranosti otporničkog djelila, kojeg čine etaloni otpora od 10 MΩ i 10 kΩ, pa je metoda mjerenja faznog pomaka između napona na donjem elementu djelila i ukupnog napona iskorištena za tu svrhu. Iz izmjerenih faznih pomaka nekompenziranog djelila izračunat je kapacitet koji treba spojiti paralelno gornjem elementu kako bi djelilo postalo kompenzirano. Zbog toga je paralelno etalonu od 10 MΩ spojen zračni kondenzator kapaciteta ugodivog od 0,1 pF do 0,7 pF pa je ponovljeno mjerenje faznog pomaka s tako ugođenim djelilom, kako bi se potvrdila njegova kompenziranost te odredila vrijednost spomenutog koeficijenta. Pritom je za omjer efektivnih vrijednosti napona "izvedenih” sinusoida od 1000:1 ostvarena nesigurnost manja od 0,1×10−6, dok je nesigurnost izmjerenog faznog pomaka manja od 0,1 µrad.
U zaključku se analiziraju ostvareni mjerni rezultati, ukazuje na smjernice za daljnji rad te za moguća poboljšanja. Pritom se navode i druge primjene opisane metode za mjerenje faznog pomaka dvama voltmetrima. Na kraju slijede prilozi, popis oznaka i uporabljene literature.
Ključne riječi: vrhunska mjerenja električkih veličina, digitalni multimetar, mjerenje izmjeničnog napona, mjerenje faznog pomaka, mjerenje omjera napona, pohranjivanje etalona, etaloni otpora i kapaciteta, mjerenje temperature, NTC otpornici, automatizirane mjerne metode.
In the Introduction, the content of each section is reviewed, developed methods are shortly described, and the achieved measurement results and their application are analysed.
High-accuracy measurements of electric quantities are described in Section Two. Thus, the establishing of SI units, the operating principle of the device for the reproduction of electrical current and voltage units, the calculable standard of capacitance, and the method for highly accurate comparison of resistance and capacitance standards are considered in this section. Quantum voltage and resistance standards, by means of which volt and ohm are nowadays maintained with the least possible uncertainty, are also discussed.
Section Three deals with the Primary Electromagnetic Laboratory within the Faculty of Electrical Engineering and Computing of the University of Zagreb. The establishment of the Laboratory is described and the system of traceability for basic electromagnetic quantities: voltage, resistance, capacitance and frequency is presented. This is followed by a detailed presentation of the reference standards that make the standard base of the Laboratory and provide traceability in accordance with the international system. These reference standards are: the electronic voltage standard with the main level of 10 V, 1 Ω and 10 kΩ resistance standards, 100 pF fused-silica and air capacitance standards, and the 100 MΩ resistance standard of own design. At the end of this section, there is a description of HP 3458A digital multimeter that can measure voltage up to 8½ digit resolution. It is the basic measuring instrument used in the methods for measurement of the effective value of low frequency ac voltage and the phase difference between two voltages. It was used in the measurements presented in Section Six.
The UTEO-97 ultrathermostat developed in the Laboratory for the maintenance of reference resistance standards is described in Section Four. NTC resistors are used for the control of temperature in that oil ultrathermostat, and in order to determine the measured temperature from each measured value of resistance, a regression curve is determined on the basis of the data given in a table. The calibration of all together 30 NTC resistors and determination of their parameters is described. The regulation of the reference temperature of 23 °C is done using a computer controlled measurement system, where the resistance of NTC sensors is measured by a digital multimeter, and a computer is used for measuring data collection, control parameters calculation, and control voltage tuning via the installed D/A interface. The temperature stability in the ultrathermostat achieved with such regulation is presented. During a single day it may be better than ±1 mK, and during a longer time period it is usually better than ±10 mK.
In Section Five, the method for calibration of the 100 MΩ resistance standard with the 100 pF capacitance standard, using computer controlled digital voltmeters HP 3458A, is presented. The method is used in the Laboratory for transfer of traceability from the domain of capacitance to the domain of resistance, i.e. C→R comparison. For that purpose a measurement bridge is made. In its one arm there is a resistance divider of 1000:1 ratio, and in the other arm, as the upper element of the divider, there is a 100 MΩ standard resistor when the measurement is done with dc current, or an air 100 pF standard capacitor when the measurement is done with ac current. In that arm, the division ratio is also 1000:1, because the lower element of the divider is a resistance standard of 100 kΩ, while digital voltmeters in both cases measure voltages in the two arms of the bridge on the lower element. Analyses show that the expected uncertainty of this method is of the order of 0,1×10−6, because it is necessary to know voltage ratios at ac and dc currents for the determination of the 100 MΩ resistance standard in relation to the 100 pF capacitance standard. A detailed analysis follows of the method for the measurement of ac voltage of 15,873 Hz frequency when the voltmeter is set to the dc voltage range, and integrates the measured ac voltage during one third of its period (21 ms). Samples are taken by shifting the beginning of integration always by the same interval, so that their values also follow the sine-wave form in the same way as the measured voltage, i.e. we can speak of a “derived” sine. Taking samples with a frequency different from the frequency of the measured voltage results in a non-integer number of samples per a period of the “derived” sine, and a method of running a polynomial of the 5th order through the sum of the squares of samples of the “derived” sine around zero is presented, by means of which the effective value of the “derived” sine is calculated in a correct way too. Determination of unknown capacitances in the arms of the bridge, using the method of connecting in parallel capacitances of known values, is described. Especially, the possibility of their determination by the measurement of the phase difference between the voltage on the lower element of the divider and the overall voltage is analysed.
Section Six contains the analysis and the results of the measurement of the phase difference between two voltages measured by HP 3458A digital voltmeters in accordance with the precepts described in the previous section. The measurement procedure is automated because the voltmeters are connected to the computer that is used for the control of measuring instruments, and for the collection, analysis and recording of measurement results. The section begins with the presentation of the method for determination of the initial phase angle of the “derived” sine, which is based on the computation of the angle for each sample of the “derived” sine, and on running the regression line through the thus computed angles. Coefficient b of that line determines the required initial phase angle, and then the phase difference between two voltages is calculated from the difference of two initial phase angles. The standard measurement procedure is described, in which digital voltmeters are used to measure two voltages of 15,873 Hz frequency from the amplitude ratio 1:1 to 1000:1, so that all together 2381 samples of the “derived” sine are taken, and for each of them the mean value, effective value and initial phase angle are calculated in order to calculate their phase difference. Because of the measurement of angles, synchronous triggering of the voltmeters is applied, where one voltmeter is the “master” and it generates triggering pulses that are transmitted to the “slave” voltmeter. For the thus calculated phase difference to be correct, it is necessary to take into account the correction, which depends on the measuring ranges to which the voltmeters are set, and on the way of triggering. The method for the determination of phase difference correction for all combinations of measuring ranges from 100 mV to 1000 V is analysed and experimentally approved. This method is based on the cascade measurement of the same voltage by two voltmeters, which are first set to the same measuring ranges, and then the measurement is repeated with one voltmeter set to the first higher measuring range. In this section, the results are given for the measurement of the phase difference correction for two pairs (four) of HP 3458A voltmeters applying the described method, with uncertainty less than 0,1 µrad. These values are used in the measurement of the phase difference of the divider that consists of the 100 pF capacitance standard and 100 kΩ resistance standard. From the measured phase difference, the unknown stray capacitance that is parallel to the resistance standard is determined, contribution to which is given also by the input capacitance of the voltmeter itself, so it can be said that the voltmeter indirectly measures its own capacitance. This measurement is necessary in order to determine one of the coefficients (correction factors) during the transition from 100 pF to 100 MΩ for the method described in Section Five. The second coefficient (correction factor) for the same method depends on the compensation of the resistance divider, which consists of resistance standards of 10 MΩ and 10 kΩ, and the method for the measurement of phase difference between the voltage on the lower element of the divider and the overall voltage is used for that purpose. From the measured phase differences of the non-compensated divider, the capacitance is calculated, which has to be connected in parallel to the upper element so that the divider becomes compensated. Therefore, an adjustable air capacitor with a capacity of 0,1 pF to 0,7 pF is connected in parallel to the 10 MΩ standard, and the measurement of the phase difference is repeated with the thus adjusted divider in order to confirm its compensation and determine the value of the mentioned coefficient. In this measurement, the achieved uncertainty of the ratio of the effective voltage values of 1000:1 ratio is less than 0,1×10−6, and the uncertainty of the measured phase difference is less than 0,1 µrad.
In the Conclusion, the achieved measurement results are analysed, and the guidelines for the continuation and possible improvements of the work are given. Other possible applications of the described method for the phase difference measurement by two voltmeters are also indicated. The last part contains appendixes, a list of symbols and references.
Key words: high-accuracy measurements of electric quantities, digital multimeter, ac voltage measurement, phase difference measurement, voltage ratio measurement, maintenance of standard, resistance and capacitance standards, temperature measurement, NTC resistors, automated measurement methods.
Bibliografija str. 212-219.